Kepastian Hukum Pada Pengajuan dan Jangka Waktu Klaim Konstruksi Berdasarkan Standar Kontrak FIDIC - Putra, Muhammad Imam Dani; Ferdi, Ferdi; Rosari, Anton (Faculty of Law, Andalas University, 2024)
In construction services law, claims or compensation are part of the construction implementation period. There are several cases where the contractor submitted the claim after the final work handover period. Claims are submitted through an arbitration institution based on the principle of separation. Apart from that, Article 1967 of the Civil Code stipulates that all material and personal legal claims are extinguished due to the expiration of thirty years. This argument makes the arbitration panel declare that the claim submission is valid. This causes legal uncertainty regarding the contract period, especially claims. The construction work contract uses FIDIC standards with specific references for submitting claims. The research methodology is empirical juridical, which emphasizes the legal awareness of the parties regarding the contract that has been agreed upon and the claim clause and whether it violates the expiration rules. The research results found that in the principle of pacta sunt servanda, the principle of freedom of contract, and the principle of justice in the construction services law, the parties have agreed to the rules regarding claims in Subclause 20.1, namely the provision that claims must be submitted in writing to the engineer within 28 days after the contractor becomes aware of an incident to claim a right. Article 1381 of the Civil Code also explicitly states that payment for achievement is one of the conditions for ending a contract, so claims should not be submitted after the final handover of work. The principle of separation of arbitration provides opportunities for contractors to submit claims even though the main contract has ended.